Political Public Relations Concepts, Principles, and Applications - Strömbäck, Jesper; kiousis, spiro (Taylor & Francis, 2020)
Frames advance coherent interpretations of issues that suggest specific problem definitions, causes, moral evaluations, and courses of action. As such, frames highlight certain aspects of an issue, and downplay or ignore others. While the use of frames is inevitable-i.e., the act of framing-actors do use frames strategically in their attempts to define issues in a way favorable to them and in their efforts to influence the course of action on issues. This is especially the case in the political realm. Thus, strategic framing is crucial to political public relations. This chapter offers a brief introduction to framing theory before shedding light on the specific ways in which political actors use frames strategically and to what effect.